Les alliances technologiques stratégiques: de la théorie à la situation canadienne - Niosi, Jorge; Bergeron, Maryse; Sawchuck, Michèle (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
Technological cooperation between business enterprises has become common-place over the past ten years or so, following an increase in the uncertainty, risk, and costs of research and development brought about by growing international competition and the unsettling impact of data processing technologies (and to a lesser degree biotechnologies) throughout the entire industrial sector. Strategies in R&D cooperation, first adopted by Japanese corporations, were copied by European firms in the early 80s and then by American and Canadian corporations later on. Governments have got in on the action through policies for encouragement of collective R&D. Current theories in economies and business administration are not very useful for understanding this phenomenon. Neo-classical economies' assumption of perfect competition, as well as dissertations on product obsolescence and transaction costs, permeate theories in business administration and do not help us comprehend this new organizational phenomenon. We have, however, come across some crucial leads towards an explanation in certain models of imperfect competition and in managerial studies on informal cooperation by businesses in R&D.